Estimativa de velocidade em meios anisotrópicos através de estereotomografia - ALCÂNTARA, Tiago Nascimento de (2019)
Isotropic stereotomography is tested to anelliptical anisotropic media. Numerical experiments using isotropic and anisotropic models show that isotropic stereotomography can be used to estimate velocity macromodel for weakly anelliptical anisotropic media. Then we will analyze the causes of information loss during the inversion.